Asuhan keperawatan pada pasien kanker payudara dengan masalah anemia menggunakan sari kurma - Sofa, Taufik; Rilyani, Rilyani; Wardiyah, Aryanti (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2024)
Background: Breast cancer is a disease resulting from abnormal cell growth in the breast, 41% of all breast cancer patients experience anemia (hemoglobin <12g/dl). Dates contain very high fiber, apart from that they also contain potassium, manganese, phosphorus, iron, sulfur, calcium and magnesium which are very good for consumption. Purpose: To provide nursing care with the intervention of giving date palm juice to breast cancer patients with anemia. Method: This research uses a descriptive research design with a case study approach to nursing care which includes assessment, diagnosis, intervention, implementation and evaluation. Results: There is an effect of applying date palm juice to increase hemoglobin in breast cancer patients. Conclusion: Peripheral perfusion nursing management was not effective in breast cancer patients with anemia by applying the date palm juice nursing action that the author carried out for 3 days and 10 days of observation found that both clients resolved everything as evidenced by the increase in hemoglobin in both clients and during the second procedure the clients were cooperative. Keywords: Breast Cancer; Date Palm Juice; Hemoglobin. Pendahuluan: Kanker payudara merupakan penyakit akibat dari pertumbuhan sel yang abnormal pada payudara, 41% dari semua pasien kanker payudara mengalami anemia (hemoglobin <12g/dl). Buah kurma mengandung serat yang sangat tinggi, selain itu juga mengandung kalium, mangan, fosfor, besi, belerang, kalsium juga magnesium yang sangat baik untuk dikonsumsi. Tujuan: Memberikan asuhan keperawatan dengan intervensi pemberian sari kurma terhadap pasien kanker payudara dengan anemia. Metode: Menggunakan desain penelitian deskriptif dengan pendekatan studi kasus asuhan keperawatan yang meliputi pengkajian, diagnosa, intervensi, implementasi dan evaluasi. Hasil: Terdapat pengaruh penerapan sari kurma untuk meningkatkan hemoglobin pasien kanker payudara. Simpulan: Pengelolaan keperawatan perfusi perifer tidak efektif pada pasien kanker payudara dengan anemia dengan penerapan tindakan keperawatan sari kurma yang penulis lakukan selama 3 hari dan observasi 10 hari didapatkan pada kedua klien teratasi semua dibuktikan kedua klien hemoglobinnya meningkat dan selama tindakan kedua klien koperatif.